A Study of the Application Sustainable Architecture at Horas Siantar Market Buildings - Roni Simarmata; N Vinky Rahman (International Journal of Architecture and Urbanism, 2023)
Pasar Horas is a traditional market with the most extensive building as a traditional market in Pematang Siantar. Pasar Horas provides all the needs of tools and household materials to meet the community's needs, which makes Pasar Horas an essential role in meeting the community's needs. The impact given by the Pasar Horas building must be considered both on the environment and its users. Pasar Horas itself has fairly bad implications when viewed from the aspect of Sustainable Architecture, such as the wrong direction of building orientation, not eco-friendly materials, inefficient land use, and waste management due to market activities, where Sustainable Architecture itself calls for the negative impact of the establishment of the building is not too big. Therefore, the application of Sustainable Architecture in Pasar Horas buildings is needed so that the negative impact caused by the market on the environment and its users can be minimized, which will later be able to adapt Pasar Horas to the new era and become a traditional market that can compete with modern markets to meet household needs of the Pematang Siantar community.